Influence of PbO molar fraction and Se doping on borate glasses - Rodríguez, M.; Aguiar, I.; Fornaro, L.; Hernandes, A. C. (Scientia Plena, 2011)
Glasses of xPbO(1-x)B2O3 composition, with x = 0.2, 0.4, 0.5 and 0.6, and doped with Se (0.01, 0.02, and 0.03 mol) were synthesized from H3BO3, PbO, Pb3O4 and Se powders, homogenized and then fused at about 700 - 800 ºC. The fused mixing was annealed at temperatures lower than the glass transition one, about 400 ºC and during 3 hours. Samples were then slowly cooled down to room temperature. PbO concentration correlates with an increase on the color intensity of the samples. Final glasses were cut, mechanical etched and then characterized by spectrometry in the 400 - 830 nm range and by differential scanning calorimetry (DSC) and thermal gravimetry (TG). The influence of PbO and Se concentrations on the spectra was confirmed studying the correlation between molar fraction and intensity of the 435 nm and 610 nm peaks. TG results indicate that, when heated up to 800 ºC, samples with Se decompose. However, sample color as far as increases for the 435 nm absorption peak, indicating the possible incorporation of Se to the glass structure. DSC diagrams show a glass transition in the 443-436 ºC temperature range. DSC also indicate the glasses have up to three crystalline phases. Future work will confirm these phases and Se incorporation by X-ray diffraction.